The Banning of Political Parties in Post-Yugoslav States. Croatian and Serbian Experience in Using Militant Democracy - Skrzypek, Maciej (Taylor & Francis, 2024)
The aim of this paper is to explore the effectiveness of a classical militant democracy instrument, as banning of extremist parties since the beginning of the political transition in 1990s in post-Yugoslav states. Comparative studies are based on Croatian and Serbian experiences, when since political transition new types of political regimes started developing as part of a boom for national parties that could guarantee consolidation of the state. The methods employed for the analysis are the qualitative analysis of sources. Corpus of sources includes national legislation, official documents, NGOs’ reports, and media content related to banning political entities. Conclusions from the study provide knowledge fill the gap in the state of art about circumstances for dissolving anti-democratic entities in the post-Yugoslav states. Moreover, they allow to verify relevant approaches and models of anti-democratic organizations, encompassing the specific types of political culture in Croatia and Serbia.
Jest to manuskrypt artykułu opublikowanego w czasopiśmie “The Banning of Political Parties in Post-Yugoslav States. Croatian and Serbian Experience in Using Militant Democracy.” Journal of Contemporary Central and Eastern Europe, 1–12. https://doi.org/10.1080/25739638.2024.2319399.
Keywords: Banning political parties; militant democracy; political parties in Serbia; political parties in Croatia